Cultural codes and brand equity relations – exploratory study and research implications - Hajdas, Monika (Kody kulturowe a kapitał marki – badanie eksploracyjne i model teoretyczny, 2019)
The aim of the paper is to explore the possible relationships between cultural brand narration and brand equity. The concept of cultural branding has been developed in marketing literature, but there are no studies showing the outcomes of building brand narrations based on residual, dominant and emergent cultural codes and whether these outcomes include effects connected with brand equity. The paper is based on multiple case research. As a result, the author suggests cultural brand narration as an independent variable, and brand equity dimensions as dependent variables. The author then forms one theory proposition and three hypotheses on the relationships between those variables. Based on multiple case research the author suggests that conservative brand narration relates negatively to brand-related effects, whereas popular and progressive brand narrations relate positively to brand-related effects.
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 1; s. 19-27
Keywords: brand equity; cultural branding; cultural codes; multiple case research; kapitał marki; kulturowa strategia marki; kody kulturowe; stadium przypadku